Which Strategies Improve Physicians' Experience with Health Information Technology? - Haskell, Jacqueline; Mandeville, Brittany; Cooper, Emily; Gardner, Rebekah (ACI Open, 2021)
Objectives While electronic health records (EHRs) have improved billing efficiency and note legibility, they may also disrupt clinical workflows, affect patient interactions, and contribute to physician burnout. This study aimed to identify effective strategies, as reported by physicians, to mitigate these EHR shortcomings.Methods The Rhode Island Department of Health administers a health information technology (HIT) survey biennially to all physicians in active practice statewide. The 2019 survey asked physicians about strategies implemented personally or by their practice to improve their experience working with HIT. Physicians who identified at least one strategy were then asked if each implemented strategy was “actually useful.”Results The 2019 survey was administered to 4,266 physicians, with a response rate of 43%. Both office- and hospital-based physicians most commonly reported that their practices had implemented voice-recognition dictation software (48 and 68%, respectively). Office- and hospital-based physicians identified self-care as the most commonly implemented personal change (48 and 47%, respectively). However, 26% of office-based and 15% of hospital-based physicians reported reducing clinical hours or working part-time to improve their experience working with HIT. The strategies identified as “actually useful” varied by practice setting and were not always the most widely implemented approaches.Conclusion Most physicians reported that both they personally and their practices had implemented strategies to improve their experience with HIT. Physicians found some of these strategies more helpful than others, and the strategies identified as most useful differed between office- and hospital-based physicians. From a workforce and access perspective, prioritizing strategies that physicians find “actually useful” is critical, as many physicians in both settings reported reducing clinical hours to improve their experience.
Keywords: electronic health records and systems; workflows and human interactions; medical informatics; burnout; professional; occupational stress